Erratum: Measurement of the absolute branching fractions for D−s→ℓ−v̄ℓ and extraction of the decay constant fDs - Lees, Jean-Pierre; Adametz, Aleksandra; Uwer, Ulrich (Physical review. D, Particles, fields, gravitation, and cosmology, 2015)
DOI:https://doi.org/10.1103/PhysRevD.91.019901